Omega-3 DHA- and EPA–dopamine conjugates induce PPARγ-dependent breast cancer cell death through autophagy and apoptosis - Rovito, Daniela; Giordano, Cinzia; Plastina, Pierluigi; Barone, Ines; De Amicis, Francesca; Mauro, Loredana; Rizza, Pietro; Lanzino, Marilena; Catalano, Stefania; Bonofiglio, Daniela; Andò, Sebastiano (Biochimica et biophysica acta, 2015)
The omega-3 docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) may form conjugates with amines that have potential health benefits against common diseases including cancers. Here we synthesized DHA-dopamine (DHADA) and EPA–dopamine (EPADA) conjugates and studied their biological effects on different breast cancer cell lines. MTT assays indicated that increasing concentrations of DHADA and EPADA significantly affected viability in MCF-7, SKBR3 and MDA-MB-231 breast cancer cells, whereas no effect was observed in MCF-10A non-tumorigenic epithelial breast cells. DHADA and EPADA enhanced Beclin-1 expression, as evidenced by immunoblotting, real-time-PCR and functional analyses. Chromatin Immunoprecipitation (ChIP) and Re-ChIP assays revealed that both compounds induced recruitment of Peroxisome-Proliferator-Activated-Receptor gamma (PPARγ) and RNA Polymerase-II at the Retinoic-X-Receptor binding region on Beclin-1 promoter. Moreover, both compounds enhanced autophagosome formation, evaluated by LC-3 and monodansylcadaverine labeling, that was prevented by the PPARγ antagonist GW9662, addressing the direct involvement of PPARγ. Noteworthy, long-term treatment with DHADA and EPADA caused the blockade of autophagic flux followed by apoptotic cell death as evidenced by PARP cleavage and DNA fragmentation in all breast cancer cells. We have provided new insights into the molecular mechanism through which PPARγ, as a central molecule in the cross talk between autophagy and apoptosis, mediates DHADA- and EPADA-induced cell death in breast cancer cells. Our findings suggest that omega-3 DHADA- and EPADA activation of PPARγ may assume biological relevance in setting novel adjuvant therapeutic interventions in breast carcinoma. •Omega-3 DHA- and EPA–dopamine (DA) conjugates inhibit breast cancer cell growth.•DHADA and EPADA as PPARγ inducers up-regulate Beclin-1 expression at transcriptional level.•DHADA and EPADA trigger autophagy and apoptosis through PPARγ in breast cancer cells